2010
DOI: 10.1002/hep.23919
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific deletion of prohibitin 1 results in spontaneous liver injury, fibrosis, and hepatocellular carcinoma in mice

Abstract: Prohibitin 1 (PHB1) is a highly conserved, ubiquitously expressed protein that participates in diverse processes including mitochondrial chaperone, growth and apoptosis. The role of PHB1 in vivo is unclear and whether it is a tumor suppressor is controversial. Mice lacking methionine adenosyltransferase 1A (MAT1A) have reduced PHB1 expression, impaired mitochondrial function, and spontaneously develop hepatocellular carcinoma (HCC). To see if reduced PHB1 expression contributes to the Mat1a knockout (KO) pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
138
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 109 publications
(152 citation statements)
references
References 29 publications
5
138
2
2
Order By: Relevance
“…Despite these findings, the mechanism of action of PHB1 as a cell proliferation control point in the liver is not clearly established. Although liver-specific Phb1 KO mice develop HCC spontaneously, this may have occurred due to the severe liver injury and regenerative response (12). Nevertheless, we observed an inverse relationship between PHB1 expression and growth in the nonmalignant AML12 hepatocyte cell line, suggesting that PHB1 plays a direct growth modulatory role (12).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Despite these findings, the mechanism of action of PHB1 as a cell proliferation control point in the liver is not clearly established. Although liver-specific Phb1 KO mice develop HCC spontaneously, this may have occurred due to the severe liver injury and regenerative response (12). Nevertheless, we observed an inverse relationship between PHB1 expression and growth in the nonmalignant AML12 hepatocyte cell line, suggesting that PHB1 plays a direct growth modulatory role (12).…”
Section: Discussionmentioning
confidence: 77%
“…PHB1 controls the H19-Igf2 axis by interacting and co-localizing with CTCF on the ICR regulatory region controlling both genes. Our previously published work showed that Phb1 KO mice develop HCC (12). To examine whether Phb1 modulation could lead to tumorigenesis in part via H19, we examined the effect of silencing or overexpressing Phb1 or H19 on proliferation of the liver cancer cell line, S-adenosylmethionine-deficient (SAMe-D), which is derived from the methionine adenosyltransferase 1a KO (Mat1a KO) mouse model of HCC (21).…”
Section: Expression Of Igf2 and H19 Negatively Correlates With Phb1 Amentioning
confidence: 99%
See 3 more Smart Citations